Absence of home-advantage in table tennis individual competitions - Paár, D.; Laczko, T. (Proceedings Book of The 16th ITTF Sports Science Congress Budapest (HUN), April 19th - 20th, 2019, 2020)
Home-advantage means that a player performs better at home field like at away field (e.g. can beat a higher ranked opponent with higher possibility). The individual competitions don`t guarantee that two players can compete in both of their own land against each other usually. The Hungarian youth and senior national team players` individual matches were examined between 2009 and 2018. In addition they were asked by a questionnaire about their feelings playing in front of the home crowd. The home-advantage wasn`t significant at the Hungarian World Tour and World Junior Circuit events by the examination of the number of gained medals. Regarding the final positions of the players the senior players in the singles competitions and the juniors in the doubles had a light home-disadvantage. 22% of the Hungarian national players think that they can do a better performance in Hungary and 17% feel that they play worst at home. There was a significant relationship between the Hungarian players` subjective feeling about their home success and their willingness to play in Hungarian international competitions. (Chi2 = 21,66, p < 0.01, Cramer V = 0.776) The results are similar like at other individual sports which means that in the individual sports with objective measured results there is no home-advantage for the players.